Sedimentation Properties of Simian Virus 40-Specific Ribonucleic Acid Present in Green Monkey Cells During Productive Infection and in Mouse Cells Undergoing Abortive Infection - Martin, Malcolm A. (1970)
The size distribution of polyribosome-associated simian virus 40 (SV40) ribonucleic acid (RNA) was examined at various times after productive infection. Eight hours after infection, virus-specific RNA was detected in the 14 to 17S region of a sucrose gradient by deoxyribonucleic acid (DNA)-RNA hybridization; RNA present in fractions sedimenting more rapidly did not react with SV40 DNA. At successively later times, SV40 RNA was detected in more rapidly sedimenting regions. By 24 hr, a portion of the SV40 RNA was detected in the 28S region, sedimenting slightly more rapidly than a MS2 RNA marker. Nuclear SV40 RNA, prepared from cells 48 hr after infection, was distributed in more rapidly sedimenting regions of the gradient, peaking at about 32 to 34S. Some nuclear virus-specific RNA could be detected in the 45 to 50S region. During the abortive infection of mouse cells, the sedimentation profile of SV40 RNA was very similar to that observed during the early phases of the lytic cycle.